THE URGENCY OF THE PROHIBITION OF POLITICAL PARTY CADRE MEMBERS FROM PARTICIPATING IN THE RECRUITMENT OF CONSTITUTIONAL JUDGES - Ayu, Putri Diah; Jufri, Muwafiq (JCH (Jurnal Cendekia Hukum), 2023)
The position of constitutional judge is one of the positions whose conditions are regulated in the 1945 Constitution. The public has questioned the election of Arsul Sani as a PPP cadre Judge from the DPR RI element because he has not resigned as a PPP cadre and member of the DPR after being approved as a Constitutional Court Judge in the DPR RI plenary session. This research aims to assess justification for phenomena that occur through legal construction. What is the urgency of limiting political party cadres for electing constitutional judges, and what is the concept of limiting political party cadres to become Constitutional Judges? This research uses normative research methods with conceptual, statutory and case approaches. The results of the research are that first, the urgency for political party cadres to be prohibited from participating in the selection of prospective Constitutional Court judges, the decisions will benefit their cronies. The second concept of limiting political party cadres to become constitutional judges does not yet have regulations. However, the prohibition on holding concurrent positions for Constitutional Judges is regulated in Article 17 of Law No. 23 of 2003 concerning the Constitutional Court. According to legal procedures and ethics, candidates for Constitutional Justice who will be nominated are not permitted to hold concurrent positions. The correct implementation of the selection and appointment of constitutional judges is that the proposed candidate should resign first from their position.